Heavy metals distribution and their correlation with physico-chemical properties of different soil series of northwestern India - Louhar, Ganpat; Yadav, Rajpaul; Pawar, Atul Bhagawan; Rekwar, Ravindra Kumar; Verma, Anil Kumar; Yadav, Dinesh Kumar (The Indian Journal of Agricultural Sciences, 2020)
A study on â€œspatial distribution of heavy metals content and physico-chemical properties of different soil series of northwestern Indiaâ€ was conducted during 2017-18 in five well established soil series which are under aeolian and upper alluvial plain of Hisar district (Haryana). The 50 surface (0-15cm) soil samples were collected with the help of GPS system (Global Positioning System) and analyzed for physico-chemical properties and availability of heavy metals (Pb, Cr, Cd, Co and Ni). The soil of different soil series of Hisar district were moderately alkaline to strongly alkaline in nature (pH 8.0-8.5), electrical conductivity (EC) ranged from 0.10-0.17 dS m-1 (non saline).The organic carbon content in soil of different soil series was low to medium (0.39-0.51%) and having sandy to sandy clay loam texture with low to moderate CEC (8.64-12.85 cmol kg-1). The calcium carbonate content in soils was < 5 %. The mean of available heavy metals such as Pb, Cr, Cd, Co and Ni ranged from 0.56-1.30, 0.03-0.17, 0.01-0.04, 0.00-0.02 and 0.03-0.16 mg kg-1 respectively, which were found below the permissible limit.